Rancang Bangun Mesin Pelontar Shuttlecock Otomatis - Ridwan, Muhammad; Rianda, Rianda; Chrysostomos Hendro Yuwono, Yohannes (entries, 2023)
This research aims to develop an automatic shuttlecock throwing machine with motion rotation system using ARDUINO UNO REV3 microcontroller, in order to increase the effectiveness of badminton training. In improving players' agility and reflexes, this system is designed to provide a long and accurate pass with a shuttlecock throwing distance of up to 10 meters, adjusting the size of the badminton court. This research includes the stages of searching for current data, detailed design planning, and manufacturing of the machine consisting of two main parts: shuttlecock throwing system and machine rotation system, with the hope that this system can function optimally in supporting badminton players' training.